Diáspora : resistência e revide em Small Island (2004), de Andrea Levy - Alves, Érica Fernandes (2010)
After the Second World War there was a considerable expansion of the diaspora around the world triggered by the independence of many colonies and by many former colonized populations to settle in the metropolis in search of a better life. In 1948 a group of Caribbeans set out for the United Kingdom to establish themselves as citizens in the metropolis, fact which is analyzed in the novel Small Island (2004), by British writer Andrea Levy, herself a descendent of Caribbean diasporic people, through the post-colonial theory, focusing on theories of diaspora and resistance. From the point of view of the theory of diaspora current research shows the motivations which lead a group of people to cross borders toward the United Kingdom that shall become their new home. It also investigates which strategies the immigrants make use of to avoid the oppression and discrimination in this country. The methodology of this research is based on studies by Van Hear (1998), Cohen (1998), Brah (2002), Hall (2006) and others. Results show that the binary scheme black/white imposed by white people rules the relationships of racism and exclusion in the society where the immigrant is established. Moreover, the immigrant resists the oppression generated by this binary scheme by being open to change and willing to negotiate with the white people so that conviviality among population may be a fact.